Maintenance of Labor at PT. Bank Sinarmas Tbk Sumedang Branch - Dewi, Kisthi Hanila (West Science Social and Humanities Studies, 2024)
This research analyzes the implementation of labor maintenance at PT Bank Sinarmas Sumedang Branch, focusing on the methods of welfare, incentives, and work environment. Welfare methods include BPJS programs, self-insurance, annual bonuses, and allowances for gasoline and vehicle servicing. In addition, incentives in the form of money and promotions are given to employees who achieve good performance. A positive and efficient work environment is also a concern, with adequate facilities, work stress management, good communication, and annual outings. This research highlights the importance of implementing workforce maintenance methods in improving employee welfare and motivation, which in turn can improve productivity and work quality.